2014
DOI: 10.1080/02786826.2014.985781
|View full text |Cite
|
Sign up to set email alerts
|

Friction Coefficient and Mobility Radius of Fractal-Like Aggregates in the Transition Regime

Abstract: The influence of geometric properties and particle size on mobility properties of fractal-like aggregates was studied in the mass and momentum-transfer transition regimes. Two methodologies were investigated. The Collision Rate Method (CRM) that determines the slip correction factor through the ratio of two fictitious Brownian particle-aggregate effective collision rates, and the Adjusted Sphere Method (ASM) that assumes the existence of a virtual, flowindependent adjusted sphere with the same slip correction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
4
14
0
Order By: Relevance
“…Figure 4 shows the K fm values of aggregates with varying k f and D f . At a fixed D f , a positive dependency between K fm and k f is clearly observed, which is in agreement with the findings of Melas et al (2014b). However, at a fixed k f , the relationship between K fm and D f is rather noisy and trivial: K fm fluctuates approximately by §3% around a mean.…”
Section: Influence Of Monomer Screening and Fractal Morphologysupporting
confidence: 81%
“…Figure 4 shows the K fm values of aggregates with varying k f and D f . At a fixed D f , a positive dependency between K fm and k f is clearly observed, which is in agreement with the findings of Melas et al (2014b). However, at a fixed k f , the relationship between K fm and D f is rather noisy and trivial: K fm fluctuates approximately by §3% around a mean.…”
Section: Influence Of Monomer Screening and Fractal Morphologysupporting
confidence: 81%
“…To do so, we extend the continuum-regime methodology introduced by Isella & Drossinos (2011), a methodology used to calculate the hydrodynamic radius of power-law aggregates (Melas, Isella, Konstandopoulos, & Drossinos, 2014a), to the slip-flow regime. The methodology may be applied to calculate the friction coefficient of fractal-like aggregates, and in general, of any non-spherical structure, as a function of the monomer Knudsen number (Melas, Isella, Konstandopoulos, & Drossinos, 2014b). Herein, it is applied to one of the simplest realizations of power-law aggregates, straight chains composed of N touching, spherical monomers of radius R 1 .…”
mentioning
confidence: 99%
“…A comparison of the predicted diffusion-equivalent spheres to the measured mobility equivalent diameters for a series of nanorods (Gopalakrishnan et al 2015b) showed excellent agreement (Tian et al 2016). Melas et al (2014Melas et al ( , 2015 investigated the friction coefficient and mobility radius of the fractal-like aggregates in the transition regime, and the application to straight chain agglomerates. These studies provided an opportunity to re-examine the high aspect ratio non-spherical particle dynamics, and the development of a convenient equivalent mobility diameter in high Knudsen number flows.…”
Section: Introductionmentioning
confidence: 85%
“…The "adjusted sphere" method has been supported by experiments (Cheng et al 1988;Rogak et al 1993), and most recently validated by Melas et al (2014Melas et al ( , 2015 For majority of the irregular-shaped particles, such as fractal-like agglomerates and straight chains, d adj is not available due to the lack of free molecular information. As a convenience, Equation (4) together with a volume equivalent diameter d ev, is frequently used to approximate the slip correction.…”
Section: Transition Regimementioning
confidence: 99%
See 1 more Smart Citation